2017
DOI: 10.1016/j.ijfoodmicro.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the baking process as a kill-step for controlling Salmonella in muffins

Abstract: This research investigates the potential risk of Salmonella in muffins when contamination is introduced via flour, the main ingredient. Flour was inoculated with a 3-strain cocktail of Salmonella serovars (Newport, Typhimurium, and Senftenberg) and re-dried to achieve a target concentration of ~8logCFU/g. The inoculated flour was then used to prepare muffin batter following a standard commercial recipe. The survival of Salmonella during and after baking at 190.6°C for 21min was analyzed by plating samples on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 10 publications
1
29
3
Order By: Relevance
“…These Salmonella serovars were selected because of their relatively high heat resistance, association with foodborne illness outbreaks, and/or isolation from low moisture food environment. The working cultures were propagated individually following the method described by Channaiah et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These Salmonella serovars were selected because of their relatively high heat resistance, association with foodborne illness outbreaks, and/or isolation from low moisture food environment. The working cultures were propagated individually following the method described by Channaiah et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The bread (300 g) and pastry (100 g) flours were weighed into a sanitized sealable plastic tub (9.4 L, Rubbermaid, Atlanta, GA), mixed, and spread into a uniform layer. Flour mix was then mist-inoculated inside the biosafety cabinet as described by Channaiah et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…It is a product created through the mixture, homogenization and convenient cooking of the dough prepared with fermented or non-fermented flours and other food items such as milk, eggs and fat (Gutkoski et al, 2009). A strong tendency of the industrialized cakes market is the snacks, small cakes wrapped in individual packaging, also called muffins (Channaiah et al, 2017;. It is noted that one of the main factors associated with poor quality in cakes is the low specific volume and the non-uniform structure of the centre, besides hardness, loss of humidity and microbial development during shelf life (Abdou et al, 2008;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The pH value obtained, 7.26, is in the range of optimum pH for Salmonella grow (6.5-7.5) (D' Aoust & Maurer, 2007;International Commission on Microbiological Specifications for Foods, 1996;Jay et al, 2005). Channaiah et al (2017), reported aw value of 0.924 ± 0.001, and pH of 6.61 ± 0.12 before cooking in Muffins batter. The higher aw values obtained in raw liquid batter of "Cavacas de Resende" can be explained by the reduced content of dry ingredients comparatively to those used in Muffins, like flour, granulated sugar, baking powder, salt, non-fat dry milk, whole egg solids and all-purpose shortening.…”
Section: Physic-chemical Determinations Before Heat Treatmentmentioning
confidence: 92%
“…In similar studies, Angelotti et al (1961) reported a D value of 11.32 min at 60 °C for S. Senftenberg 775W inoculated in custard. Besides, Channaiah et al (2017), inoculated a cocktail of S. Newport, S. Typhimurium and S. Senftenberg 775W, in flour that was mixed with the remaining ingredients to cook Muffins, obtained D values of 62.16 ± 2.99 min, 40.09 ± 0.88 min and 16.46 ± 1.71 min, at 55, 58 e 61 °C respectively, with a z value of 10.40 ± 0.63 °C. It can be verified that the values reported by these authors are higher than the values showed in Figures 1 and 2.…”
Section: And Z Valuesmentioning
confidence: 99%